Isolation and Antibacterial Activity of Alkaloids from Phaeanthus opthalmicus - Atan, M.S.; Dzulkefly, K.A.; Mohd Aspollah, S.; Anuar, K.; Vijay, S. (Asian Journal of Chemistry, 2011)
Four alkaloids; O-methyldauricine (1), limacine (2), corydaldine (3) and oxostephanine (4) were isolated from Phaeanthus opthalmicus and their structures have been fully characterized by spectral methods. Antibacterial activities of the pure compounds 1, 2 and 3 have also been assessed. This is the first report of the presence of compounds 1, 3 and 4 in this genus.